1993
DOI: 10.1002/pro.5560020610
|View full text |Cite
|
Sign up to set email alerts
|

ATP binding to cytochrome c diminishes electron flow in the mitochondrial respiratory pathway

Abstract: Eukaryotic cytochrome c possesses an ATP-binding site of substantial specificity and high affinity that is conserved between highly divergent species and which includes the invariant residue arginine''. Such evolutionary conservatism strongly suggests a physiological role for ATP binding that demands further investigation. We report the preparation of adducts of the protein and the affinity labels 8-azido adenosine 5'-triphosphate, adenosine S-triphosphate-T,3'-diaIdehyde, and 5'-p-fluorosulfonylbenzoyladenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…A high affinity binding site for ATP has been described and shown to involve the invariant Arg 91 (5,(7)(8)(9)(10). The involvement of Arg 91 in binding of ATP and consequent modulation of electron transfer by the protein has been investigated previously by semisynthetic analogs of cyt c in which this single arginine residue of the 66 -104 peptide was chemically modified by cyclohexane-1,2-dione prior to ligation with the 1-65 peptide (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high affinity binding site for ATP has been described and shown to involve the invariant Arg 91 (5,(7)(8)(9)(10). The involvement of Arg 91 in binding of ATP and consequent modulation of electron transfer by the protein has been investigated previously by semisynthetic analogs of cyt c in which this single arginine residue of the 66 -104 peptide was chemically modified by cyclohexane-1,2-dione prior to ligation with the 1-65 peptide (10).…”
Section: Discussionmentioning
confidence: 99%
“…In cyt c part of the high affinity ATP-binding site is constituted by the invariant Arg 91 (5,(7)(8)(9)(10), and binding of ATP to this decreases the rate of electron flow through the mitochondrial electron transport chain (9). Accordingly, when the ATP-binding site of cyt c is occupied by a covalently bound ATP, the electron-transfer activity of cyt c with reductase and oxidase are inhibited to 41 and 11-15%, respectively, of the values measured for the native protein (3).…”
mentioning
confidence: 99%
“…Previous studies have shown that, contrary to yeast, horse cyt c possesses (at least) one binding site with high affinity for ATP [18,19,37]. This is correlated with the critical role played by cyt c in cell apoptosis.…”
Section: Effect Of Atp On Complex Formation/dissociationmentioning
confidence: 97%
“…It has been shown that anions directly bind cytochrome c around the polylysine binding pocket [13,14]. This binding of ATP may be physiologically important for feedback inhibition of the respiratory chain [15].…”
mentioning
confidence: 99%